Several Medicinal Plant Species Need Enrichment Planting - Andianto; Agus Ismanto; Rosi M. Tampubolon (The Ethnobiological Society of Indonesia, 2022)
Pulai (Alstonia scholaris), kayu manis/cinnamon (Cinnamomum burmanii, Cinnamomum iners), pakanangi/kisereh (Cinnamomum parthenoxylon/Cinnamomum porrectum), kulilawang (Cinnamomum halmaherae), agarwood (Aquilaria sp., Gyrinops versteeghii, and Gyrinopsis cumingiana), and pasak bumi (Eurycoma longifolia) are some medicinal plants species that grow in plantations or natural forests. The exploitation of these species causes their existence to be scarce or almost not known, with the result that is needed the policy to save the existence of medicinal plants species. Industries of herbal medicine which exploit the raw material from nature need to build seedlings and enrichment areas. The collaboration between medicinal industries with local people to build medicinal plant species plantations can be developed. This study informs a field review of some medicinal plant species from several regions during the research activities from 2005 to 2009.